2004
DOI: 10.1111/j.1523-1755.2004.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal blood pressure is elevated with natriuresis and proteinuria as renal function deteriorates in nephropathy

Abstract: Our results show that as renal function deteriorates in glomerulopathy the nocturnal dip in blood pressure is lost, resulting in enhanced urinary sodium and protein excretions during night. These findings are compatible with our proposal that impaired natriuresis during daytime makes nocturnal blood pressure elevated to compensate for diminished natriuresis by pressure natriuresis. We speculate that nocturnal glomerular capillary hypertension contributes, at least in part, to enhanced urinary sodium and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
114
4
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(126 citation statements)
references
References 31 publications
5
114
4
1
Order By: Relevance
“…Low eGFR and proteinuria were associated with elevated nighttime BP. These results are consistent with earlier studies in cohorts of patients with CKD, and highlight the importance of ABP rather than home BP in assessing the potential effect of hypertension in patients with CKD (14)(15)(16). Additionally, use of diuretics and angiotensin converting enzyme inhibitors and/or angiotensin receptor blockers was associated with lower nighttime BP.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Low eGFR and proteinuria were associated with elevated nighttime BP. These results are consistent with earlier studies in cohorts of patients with CKD, and highlight the importance of ABP rather than home BP in assessing the potential effect of hypertension in patients with CKD (14)(15)(16). Additionally, use of diuretics and angiotensin converting enzyme inhibitors and/or angiotensin receptor blockers was associated with lower nighttime BP.…”
Section: Discussionsupporting
confidence: 91%
“…Cross-sectional analyses in patients with normal renal function show that elevated nighttime BP is associated with both greater pulse wave velocity (PWV) and LVH (3,12,13). A few small studies of patients with CKD have shown that both decreased eGFR and proteinuria are associated with elevated nighttime BP (14)(15)(16). The mechanism by which CKD leads to elevated nighttime BP is not well understood but is likely multifactorial, and includes volume-dependent hypertension exacerbated by recumbent posture, abnormal sodium handling, and comorbidities such as diabetes and autonomic insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that the RI was a useful predictor of renal dysfunctions [11][12][13][14][15][16] and correlated significantly with organ damage. Measurement of RI in addition to low-grade albuminuria is reportedly useful for target organ damage screening in patients with resistant Blood pressure variability and renal function T Kawai et al hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…[11][12][13][14][15][16] We previously reported that the RI might be a more efficacious parameter for the evaluation of very early renal damage than estimated glomerular filtration rate (eGFR). 17 It is thought that renal vascular damage caused by atherosclerotic risk factors such as hypertension and variability of BP could be evaluated more precisely by the RI.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Chronic kidney disease (CKD) seems to be tightly linked with nocturnal hypertension and morning BP surge. 7 CKD poses a high risk for the onset of cardiovascular disease. Early detection and appropriate treatment delays the progression of kidney disease and prevents the incidence of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%